Malware forensics : investigating and analyzing malicious code - Aquilina, James M. (Syngress Pub., 2008)
'Malware Forensics' covers the emerging and evolving field of 'live forensics, ' where investigators examine a computer system to collect and preserve critical live data that may be lost if the system is shut down.